Developing realistic problem-based mathematics instructional materials to enhance students' conceptual understanding (Asian Journal of Educational Technology, 2022)
The purpose of this research was to develop realistic problem-based instructional materials that were both valid and practical in order to assist students in successfully enhancing their conceptual comprehension. We adopted the Borg and Gall's research and development model. During the process, we involved a total of seven teachers and 196 fifth-grade students in a public elementary school in Bandar Lampung, Lampung Province on the Indonesian island of Sumatra. We used several instruments including observation, questionnaire, and tests for data collection followed by descriptive statistics, t-test, and proportion test to test the effectiveness of the instructional materials being developed. The findings suggest that the realistic problem-based mathematics instructional materials that were developed are valid and practical to use. In other words, the instructional materials successfully help fifth-grade students enhance their conceptual comprehension. Following the findings are a discussion of the limitations and suggestions for future research